The Impact of Digital Marketing on Financial Performance (Study of Halal Tourism Destinations on Madura Island) - Kompyurini, Nurul; Haryadi, Bambang; Bullah, Habi (Journal of International Conference Proceedings, 2023)
The purpose of this study is to find empirical evidence about the effect of digital marketing on the financial performance of tourist destinations on Madura Island. The approach used in this research is quantitative research. The research population is halal tourist destinations on Madura Island. While the sample has been selected as many as 100 tourist destinations. The data were processed using Smart PLS SEM (Partial Least Square - Structural Equation Modeling) software. Based on the results of the research discussion above, the conclusion of this study is that digital marketing impacts financial performance, this means that by implementing good digital marketing, the financial performance of halal tourism will be better.